EFEKTIVITAS PISANG AMBON (MUSA PARADISIACA.L) TERHADAP FREKUENSI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I - Desmariyenti Desmariyenti (Akademi Kebidanan SEMPENA NEGERI Pekanbaru, 2022)
ABSTRACTEmesis gravidarum is a complaint that is often experienced by pregnant womenin the first trimester, and can become hyperemesis gravidarum thereby increasingthe risk of pregnancy disorders. Ambon banana is an herbal plant that has longbeen known to prevent nausea and vomiting. The purpose of this study was todetermine the effect of Ambon banana on the frequency of nausea and vomitingin first trimester pregnant women in the work area of Payung Sekaki HealthCenter Pekanbaru in 2021. The type of research carried out was quantitativewith the design of this study was quasi-experimental with pre-test and post-testdesigns. The total population in this study were 34 pregnant women,the sampling technique used purposive sampling with a sample of 15 pregnantwomen. The data analysis used was univariate and bivariate using PairedSample t Test. The results of this study indicate that there is a differencein the average frequency of nausea and vomiting before and after the Ambonbanana intervention. Bivariate results show P value 0.000 and 0.05,meaning that there is an effectiveness of Ambon banana on the frequencyof emesis gravidaru in first trimester pregnant women. It is hoped that thecommunity can use Ambon banana as an alternative treatment beforeusing antiemetic drugs, and can process other variants of the banana plant.which can be used to reduce the frequency of emesis gravidarum.